Understanding Healthcare Resource Allocation in Epidemic and Pandemic Situations: The role of COVID-19 and ethics as driving forces for research - Mejia-Salazar, Max Kevin (2023)
Introduction: The allocation of healthcare resources during epidemic and pandemic events is a complex challenge that requires careful decision-making. Fair distribution of resources like masks, ventilators, and vaccines is crucial, and allocation strategies aim to maximise efficiency. Rationing in healthcare raises ethical concerns, particularly for vulnerable groups. We aimed to analyse the research landscape in healthcare resource allocation during epidemics and pandemics, providing insights to inform researchers in developing evidence-based and ethical decision-making frameworks. Material and methods: We conducted a bibliometric analysis on journal articles indexed in the Web of Science and Scopus databases with English language abstracts. A systematic search strategy was developed using relevant keywords. Data were processed and analysed for descriptives, citation analysis, co-citation analysis, and social network analysis. Results: An analysis including 124 documents found a significant increase in research output in this field in recent years, with most articles published between 2019 and 2022. The United States emerged as the leading country in terms of research output. COVID-19, ethics, and triage were revealed as prominent themes and topics such as. The findings highlight the importance of ethical considerations and the impact of the COVID-19 pandemic on driving research in healthcare resource allocation. The study highlights the prominence of COVID-19 as a driving force for research and the importance of ethics-related journals as sources of knowledge. The analysis also identifies potential opportunities for international collaboration. Conclusion: the study enhances our understanding of resource allocation in healthcare during crisis events and provides valuable insights for researchers in developing informed decision-making frameworks.